2003
DOI: 10.1152/japplphysiol.01016.2002
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic exercise training reduces plasma endothelin-1 concentration in older women

Abstract: Endothelial function deteriorates with aging. On the other hand, exercise training improves the function of vascular endothelial cells. Endothelin-1 (ET-1), which is produced by vascular endothelial cells, has potent constrictor and proliferative activity in vascular smooth muscle cells and, therefore, has been implicated in regulation of vascular tonus and progression of atherosclerosis. We previously reported significantly higher plasma ET-1 concentration in middle-aged than in young humans, and recently we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
115
5
11

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 177 publications
(143 citation statements)
references
References 54 publications
12
115
5
11
Order By: Relevance
“…33,34) Increased blood pressure 35) or increased ET-1 production 17) have unfavorable effects on the arterial walls. Maeda, et al 36,37) previously reported that the plasma level of ET-1 was decreased by aerobic exercise training in young and elderly humans. In this study, we observed that participation in endurance exercise had more of an effect on the plasma level of ET-1 than the effect caused by essential hypertension.…”
Section: Discussionmentioning
confidence: 98%
“…33,34) Increased blood pressure 35) or increased ET-1 production 17) have unfavorable effects on the arterial walls. Maeda, et al 36,37) previously reported that the plasma level of ET-1 was decreased by aerobic exercise training in young and elderly humans. In this study, we observed that participation in endurance exercise had more of an effect on the plasma level of ET-1 than the effect caused by essential hypertension.…”
Section: Discussionmentioning
confidence: 98%
“…Two studies in small groups of young and elderly Japanese subjects have reported significant reductions in plasma EDN1 levels after 2 to 3 months of endurance training. 31,32 Also, EDN1 mRNA levels in the heart were significantly lower in exercise-trained (12 weeks) spontaneously hypertensive rats than in sedentary control animals. 33 However, in normotensive Wistar-Kyoto rats, EDN1 expression in the heart either tended to decrease or increase after exercise training.…”
Section: Rankinen Et Al Edn1 Blood Pressure Activity and Fitnessmentioning
confidence: 97%
“…The muscle blood flow represents only 15-20% of the resting cardiac output, but during maximal exercise increases to approximately 85% of total cardiac output. With aging, neural activity [60][61][62] and endothelin-1 concentration 63) increase, while endothelial function [64][65][66] , aortic distensibility 67) , and capillary number decrease 8-11) . Moreover, erythrocyte-mediated ATP release, which mediates vasodilation during conditions of erythrocyte deoxygenation, decreases with aging 68) .…”
Section: Loss Of Blood Flow Volume With Agingmentioning
confidence: 99%